(untitled) (Research, Society and Development, 2020)
With the evolution of bacterial resistance over conventional antimicrobials and the development of new antimicrobials, the search for new compounds of natural origin has intensified, since plants with therapeutic potential constitute a source of new biologically active compounds, encouraging the development of new therapeutic options. The objective of this study was to evaluate the antibacterial and anti-adherent activity of the ethanolic extract of Praxelis clematidea (Griseb.) R.M. King & Robinson (Asteraceae) on strains of Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa and Enterococcus faecalis. Tests were carried out to determine the MIC and MBC by means of broth microdilution in 96-well plates, and to determine the MICA, a technique with inclined tubes in the presence of 5% sucrose was used. It was observed that the ethanolic extract of P. clematidea has strong bactericidal activity on K. pneumoniae, and moderate bactericidal activity on S. pneumoniae and E. faecalis. Being able to inhibit adherence to K. pneumoniae strains. Thus, the ethanolic extract of P. clematidea proves to be effective as an antimicrobial in the control and prevention of infections by S. pneumoniae, K. pneumoniae and E. faecalis. It also has an effective anti-adherent effect on K. pneumoniae strains.